AL-QUR'AN LITERACY PROGRAM: A SOLUTIVE EFFORT TO STRENGTHEN STUDENTS' INTEREST IN LEARNING? - Mardiana, Dina (Universitas Nurul Jadid, 2023)
The focus of this research lies in strengthening students' interest in learning through the Al-Qur'an literacy program at MAN 1 Tapin. As a school intracurricular activity, the Al-Qur'an literacy program has contributed to strengthening students' interest in learning. Based on Hellmut W. Krapp's cognitive theory, this research relies on a qualitative approach with the type of case study research. Data collection was carried out by observation, interview and documentation techniques. The results of the study concluded that MAN 1 Tapin has a Qur'an literacy program that is capable of being an alternative solution in increasing students' interest in learning, based on two things. First, the form of Qur'an literacy activities that are easy and relevant for students, and second, the presence of consistent supporting activities for the Qur'an literacy program, namely